Designing Asynchronous Digital Media for Teaching Reading Comprehension by Implementing Task-Based Learning - Edi Sunjayanto Masykuri; Kostina Ekaterina Alekseevna; Ismawati Ike Nugraeni (Journal of Education and Teaching (JET), 2025)
Reading is a crucial skill in learning English that students must master. However, learners often face challenges such as limited time and restricted access to reading materials. In the Russian Federation, website restrictions further limit access to educational resources. This study addresses the issue by introducing visual storybooks as a solution to enhance students' reading comprehension. The research was conducted with first-semester students at Novosibirsk State Pedagogical University, involving 22 participants. Using a classroom action research design, the study aimed to test the hypothesis that visual storybooks can significantly improve reading comprehension. Data were collected through reading tests, and the learning process incorporated small group discussions to foster idea sharing and active participation. The results showed notable improvement in students' reading comprehension scores, with pre-test results averaging 72.04 and post-test results reaching 81.81. The findings indicate that visual storybooks effectively enhance reading comprehension and engagement among first-semester students in the Russian Federation.